Hydrophilic tripeptide-functionalized magnetic metal–organic frameworks for the highly efficient enrichment of N-linked glycopeptides. Issue 25 (19th June 2018) - Liu, Qianjing; Deng, Chun-hui; Sun, Nianrong
Abstract : The synthetic procedure of hydrophilic metal–organic frameworks by modifying glutathione on Au-immobilized magnetic MOFs. Abstract : Hydrophilic interaction liquid chromatography (HILIC) is a useful tool in glycoproteomic analysis. Glutathione (GSH) is a well-known zwitterionic tripeptide with great hydrophilicity and biocompatibility and is ubiquitous in biological activities. In this study, a hydrophilic metal–organic framework (denoted as mMOF@Au@GSH) was synthesized by grafting glutathione on Au-immobilized magnetic MOFs via the affinity between the thiol group in glutathione and Au. Endowed with the high hydrophilicity of glutathione, the large surface area of the MOF and strong magnetic responsiveness of magnetic nanoparticles, the as-prepared mMOF@Au@GSH exhibited high selectivity (1 : 100) and great sensitivity (0.5 fmol μL −1 ) towards glycopeptides. Furthermore, it also achieved outstanding performance in enriching glycopeptides from complex biological samples. In all, 273 glycopeptides corresponding to 94 glycoproteins were identified from only 2 μL human serum.